Assessing the effectiveness of embedding CFRP laminates in the near surface for structural strengthening - Barros, Joaquim A. O. (2006)
The authors of the present work wish to acknowledge the support provided by the S&P, Bettor MBT Portugal, Secil, Nordesfer, Ferseque, Casais, Solusel, VSL, Unibetão (Braga) and the colaboration of Cemacom.